L'Alto Tigri nelle età del Bronzo Antico e Medio Siti, sequenze e ceramiche rosso-brune tra fine III e inizio II mill. a.C. - D'Agostino, Anacleto (Studia Asiana, 2016)
The region crossed by the upper course of the Tigris River, in south-eastern Turkey, has long been an area little known from an archaeological point of view. The intensification of field research, starting from the nineties of the last century, has produced the evidence on which to base a first reconstruction of the history of the settlement and of the material culture of these territories, located between the high Anatolian-Eastern lands and the Mesopotamian plains. The results of the excavations and field surveys indicate that between the end of the Ancient Bronze Age and the beginning of the Middle Bronze Age a process of transformation and reorganisation of the local communities matured. The appearance of large architectural complexes and buildings in medium-small sites, characterised by particular sets of objects and red-brown ceramics, could reveal the development of socio-political realities more structured than those of the previous period. Moreover, this could be an expression of the Khurrite world which, according to historical studies, would locate one of its main settlement areas in the Tigris region.